Two Theories of Divine Conservation - Pruss, Alexander R. (Proceedings of the American Catholic Philosophical Association, 2022)
I explore the connections between presentist and non-presentist theories of time and the doctrine of divine conservation. Presentism naturally leads to the idea that causation must be simultaneous, which makes diachronic causal chains problematic. Divine conservation, however, allows one to extend simultaneous causation into diachronic chains, but at the expense of introducing a certain measure of occasionalism. This occasionalism can be removed at the expense of making all diachronic causal series indeterministic. On the other hand, a non-presentist (eternalist or growing block) theory of time allows for a very different concurrentist theory of divine conservation. This theory appears somewhat superior to the presentist one, which gives the classical theist some reason to prefer non-presentism.